2012
DOI: 10.1111/j.1532-5415.2012.03920.x
|View full text |Cite
|
Sign up to set email alerts
|

Potentially Avoidable Hospitalizations of Dually Eligible Medicare and Medicaid Beneficiaries from Nursing Facility and Home‐ and Community‐Based Services Waiver Programs

Abstract: Potentially avoidable hospitalizations are common and costly in the dually eligible population. New initiatives are needed to reduce PAH in this population as they are costly and can adversely affect function and quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
238
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 198 publications
(246 citation statements)
references
References 18 publications
7
238
1
Order By: Relevance
“…This study identified potentially avoidable hospitalizations using the same logic and diagnosis codes described in Walsh, Freiman, Haber, Bragg, Ouslander, & Wiener (2010). The algorithm was developed by a technical expert panel that was sponsored by the Centers for Medicare & Medicaid Services (CMS) and included experts in geriatrics, ambulatory care sensitive conditions, and other quality measures.…”
Section: Potentially Avoidable Hospitalization Algorithmmentioning
confidence: 99%
“…This study identified potentially avoidable hospitalizations using the same logic and diagnosis codes described in Walsh, Freiman, Haber, Bragg, Ouslander, & Wiener (2010). The algorithm was developed by a technical expert panel that was sponsored by the Centers for Medicare & Medicaid Services (CMS) and included experts in geriatrics, ambulatory care sensitive conditions, and other quality measures.…”
Section: Potentially Avoidable Hospitalization Algorithmmentioning
confidence: 99%
“…These conditions considered as potentially preventable or manageable within the nursing home setting were developed by a technical expert panel in a study funded by CMS [32]. …”
Section: Incontinencementioning
confidence: 99%
“…Hospitalizations of nursing home residents are common. Research has suggested that 31-45% of these hospitalizations may be avoidable or manageable within the nursing facility with appropriate care [29][30][31][32]. In 2010, more than 90% of all certified facilities were cited for one or more deficiencies and nearly one-fourth of all certified facilities were cited for deficiencies that caused actual harm or immediate jeopardy to residents [9].…”
Section: Evidence Of Low Quality In Nursing Homes and Changes In Qualmentioning
confidence: 99%
“…Reducing HF hospital readmission rates from SNF and NH has become a national priority because approximately 20% of these patients are Medicare beneficiaries and are readmitted within 30 days [4]. Readmissions are multifactorial and problematic in this unique population because of high cost, and disruptions in care, disease progression, and increased mortality.…”
mentioning
confidence: 99%
“…In order to decrease costs, the National Quality Forum has endorsed hospital risk-standardized readmission rates (RSRRs) as performance measures [3]. The patient protection Affordable Care Act 2010 created incentives to reduce readmission, with penalties for hospitals which included zero reimbursement for services provided and/or loss of revenue if the HF patient is readmitted within 30 days [4]. Hospitals with high readmission rates may be subject to lose ~3% of their Medicare reimbursement by 2015 [3].…”
mentioning
confidence: 99%